Characteristics of technological base, pace of technological development, and growth of young technology-based firms - Joachim Tischler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Young technology ventures are strongly affected by technological environmental conditions. In the light of opportunity theory, this study focuses on the interaction of a young firm's technological base and the pace of technological development in its field. It distinguishes three technological characteristics: radicalness, scope, and the degree of collaborative development. Empirical results support the hypothesis that young technology-based firms commercializing radical technologies grow faster in rapidly developing technology fields. By contrast, young firms commercializing technologies that are developed through research collaborations with established firms outperform others when the pace of technological progress is relatively slow. This study provides empirical evidence of a beneficial interplay between technological characteristics and technological environment and offers a modified patent-citation-based criterion for measuring the pace of technological development in different technology fields.
Keywords: L25; L26; M13; O33; 650; academic spin-off; technology venture; pace of technological progress; patent data; technological base